Management of upper gastrointestinal bleeding - I. Govender; S. Rangiah; H. I. Okonta (South African Family Practice)
This paper will describe the common symptoms, signs and causes of upper gastrointestinal bleeding. We will then provide advice on the management of upper gastrointestinal bleeding at primary care level.